Effect of freezing and drying processes on the molecular traits of edible yellow mealworm. (August 2018) - Melis, Riccardo; Braca, Angela; Mulas, Gilberto; Sanna, Roberta; Spada, Simona; Serra, Giuseppe; Fadda, Maria Leonarda; Roggio, Tonina; Uzzau, Sergio; Anedda, Roberto
Abstract: Yellow mealworm ( Tenebrio molitor L.) represents a highly sustainable source of proteins for food and feed. Industrial production of mealworm meals for food and feed must count on optimized processing methods based on a deep knowledge of nutritional and quality aspects. Viable mealworm larvae (VL) were frozen at −20 °C and dried under two different thermal conditions, namely high-temperature-short-time (HTST, 90 °C for 1.5 h) and low-temperature-long-time (LTLT, 50 °C for 62 h). Proximate composition, fatty acid analyses by gas-chromatography and metabolic profiling by means of proton nuclear magnetic resonance ( 1 H NMR) spectroscopy were carried out and 1 H NMR data investigated with multivariate data analysis (MVDA). While fatty acid profiles did not indicate significant differences among treatments, 1 H NMR highlighted relevant molecular alterations associated to LTLT drying (95% of detected metabolites are altered by LTLT). In particular, detrimental hydrolysis of triacylglycerols (TAG) was favored during LTLT drying (approximately 25% reduction of TAG in LTLT compared to VL), accompanied by the enrichment of the free amino acid pool. Larvae composition was only minimally affected by the freezing process, with only 15% of the metabolite pool affected. Industrial relevance: Sustainable industrial production of insect-derived products (insect meal, oil, and other extracts) must count on efficient processes and high standard quality. Freezing and drying are the most critical processing operations in insect industry, since they can strongly affect the quality of final products. It is demonstrated here that low-temperature-long time drying processes negatively affect insect products quality, while freezing and high-temperature-short time drying do not have a significant impact. Molecular details of nutrient degradation processes are provided. Highlights: Technological processes affect quality traits (color, carbohydrate, lipid and amino acid profiles) of yellow mealworm larvae 95% of metabolites are altered by low-temperature drying (LTLT), 30% by high-temperature drying (HTST), only 15% by freezing LTLT significantly (P < 0.05) favors lipid hydrolysis and proteolysis, freezing leads to breakdown of cell membrane (P < 0.05) High-temperature-short-time drying should be preferred to preserve insect meal compositional quality as unaltered as possible